Novel endotypes in heart failure: effects on guideline-directed medical therapy. (13th December 2018) - Tromp, J; Ouwerkerk, W; Demissei, B G; Anker, S D; Cleland, J G; Dickstein, K; Filippatos, G; van der Harst, P; Hillege, H L; Lang, C C; Metra, M; Ng, L L; et al.
Abstract: Aims: We sought to determine subtypes of patients with heart failure (HF) with a distinct clinical profile and treatment response, using a wide range of biomarkers from various pathophysiological domains. Methods and results: We performed unsupervised cluster analysis using 92 established cardiovascular biomarkers to identify mutually exclusive subgroups (endotypes) of 1802 patients with HF and reduced ejection fraction (HFrEF) from the BIOSTAT-CHF project. We validated our findings in an independent cohort of 813 patients. Based on their biomarker profile, six endotypes were identified. Patients with endotype 1 were youngest, less symptomatic, had the lowest N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels and lowest risk for all-cause mortality or hospitalization for HF. Patients with endotype 4 had more severe symptoms and signs of HF, higher NT-proBNP levels and were at highest risk for all-cause mortality or hospitalization for HF [hazard ratio (HR) 1.4; 95% confidence interval (CI) 1.1–1.8]. Patients with endotypes 2, 3, and 5 were better uptitrated to target doses of beta-blockers ( P  < 0.02 for all). In contrast to other endotypes, patients with endotype 5 derived no potential survival benefit from uptitration of angiotensin-converting enzyme-inhibitor/angiotensin-II receptor blocker and beta-blockers ( P interaction <0.001). Patients with endotype 2 (HR 1.29; 95% CI 1.10–1.42) experienced possible harm from uptitration of beta-blockers in contrast to patients with endotype 4 and 6 that experienced benefit ( P interaction for all <0.001). Results were strikingly similar in the independent validation cohort. Conclusion: Using unsupervised cluster analysis, solely based on biomarker profiles, six distinct endotypes were identified with remarkable differences in characteristics, clinical outcome, and response to uptitration of guideline directed medical therapy.